Comparative Efficacy of Four Stain Removal Methods for Bleach-Shade Composite Resins after Immersion in Staining Solutions: An In Vitro Study - Sedighe Sadat Hashemikamangar; Shakiba Farahani; Shaghayegh Khoshgoo; Parisa Doroudgar (International Journal of Dentistry)
Introduction. Bleach-shade composite resins were recently introduced to the market due to the high demand of patients for whiter teeth. This study sought to compare four stain removal methods for bleach-shade composite resins. Materials and Methods. Seventy-two discs were fabricated from each of the Filtek Z350 XT and Gradia XBW composite resins and immersed in coffee or sour cherry juice staining solutions. Each group was then divided into four subgroups to assess the efficacy of four stain removal methods (finishing with soft-lex disk “brush with pumice” bleaching with carbamide peroxide 16%, bleaching with hydrogen peroxide 40%). The color of each specimen was measured by Easyshade spectrophotometer, and data were analyzed using SPSS 25 statistical package for social sciences. Results. The home-bleaching technique was more effective than the office-bleaching and pumice for the removal of sour cherry juice stain (ΔE = 1.93) and coffee stain (ΔE = 3.32) from Gradia composite discs, almost returning the baseline original color. The Sof-Lex discs were more effective than the pumice for the removal of sour cherry juice stain (ΔE = 4.11) and coffee stain (ΔE = 4.93) from Z350 composite discs but not return the baseline original color. Conclusions. Filtek Z350 had more discoloration than Gradia Direct. The different materials and solutions reacted differently to the four stain removal methods. In GCJ group after all stain removal methods, ΔE reduced to a clinically acceptable level.